Pengaruh Working Capital Turn Over, Recievable Turn Over ter-hadap Laba Bersih pada Perusahaan Sub Sektor Logam yang terdaftar di BEI - yopi irwan gulo (Universitas HKBP Nommensen, 2023)
This research aims to determine the effect of Working Capital Turn Over, Receivable Turn Over on Net Profit. The type of research used in this research is quantitative research with a casual associative approach with secondary data types. The population in this study were all 17 metal and similar sub-sector companies listed on the Indonesia Stock Exchange using a purposive sampling method. Based on the determination of these criteria, there were 14 companies that became the research sample with a total of 56 observations. The research results show that Working Capital Turn Over has a negative and significant effect on net profit, and Receivable Turn Over has a negative and significant effect on net profit.